To determine the expression that the graph of the additive rule represents, we can analyze the points given: (2, 39) and (4, 41).
An additive function can be expressed in the form of \(y = x + c\), where \(c\) is a constant.
From the first point (2, 39):
- When \(x = 2\), \(y = 39\), so: \[ 39 = 2 + c \implies c = 39 - 2 = 37 \] Therefore, the expression could be \(y = x + 37\).
From the second point (4, 41):
- When \(x = 4\), \(y = 41\), so: \[ 41 = 4 + c \implies c = 41 - 4 = 37 \] This also confirms that \(c = 37\).
Thus, both points indicate that the expression the graph represents is: \[ y = x + 37 \]
So the final answer is: x + 37.